Physical activity and obesity - Bouchard, Claude; Katzmarzyk, Peter T. 1968- (Human Kinetics, 2010)
Physical Activity and Obesity, Second Edition, addresses an array of topics that explore and divulge the links between physical activity (or inactivity) and obesity. Leading scientists from various backgrounds team up to provide an unrivaled resource examining the latest research and developments in the field. Each chapter provides researchers and practitioners with a clear explanation of the concepts, research techniques, and results of studies critical to understanding physical activity and the obesity epidemic. In the 10 years since the first edition of this book was published, the field of physical activity and obesity has mushroomed with new research, sparking the need for not only a new edition but an innovative and refreshing approach to the contents. Editors Bouchard and Katzmarzyk create a go-to resource with 89 succinct, authoritative chapters that may be used independently or as a complete text. Packed with the most up-to-date information linking obesity and physical activity, this comprehensive book: delves into areas of uncertainty and controversy instead of avoiding them or skirting the issues; emphasizes, where appropriate, the underlying mechanisms between physical activity and obesity; and points to research areas that need further exploration and attention. The nine parts of the book flow logically and address obesity in all populations, including children and adults of various backgrounds, ethnicities, and social classes. An overview of the methods used in assessing the levels of sedentary behavior and physical activity is given, followed by a global view of the problem of physical inactivity and obesity. Readers will learn about the key determinants of physical activity levels and obesity and the links between a sedentary lifestyle and the risk of obesity. Other topics examined include behavioral and environmental correlates and determinants of obesity, the relationship between low physical activity energy expenditure and obesity risk, clinical implications, and policy and research issues related to physical activity and obesity. Physical Activity and Obesity, Second Edition, helps readers better understand the role of physical activity in the overall energy balance equation. The unique format, expert contributors, and complete references make this resource indispensable for researchers, health and exercise practitioners, and students studying the ever-expanding topic of obesity as it relates to physical activity.